Radikalisme Islam di Jantung Kota Santri: Fragmentasi dan Polarisasi - Aripudin, Acep (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2020)
Tasikmalaya has a problem with the emergence of hardline Islamic movements, which sometimes bring out the face of "radical" Islam. The movement was responded by some people, so that it seemed to have the support of the people. They carry out social, political and mass mobilization activities to claim their rights in the name of religion. They put pressure on the local government by bringing up the issue of the Sharia local regulation. This research explores several Islamic mass organizations in the City of Santri, Tasikmalaya. This research study related to the Islamist movement is focused on the polarization and pragmentation of its movement, representing the theme of discourse related to the thoughts and activities of religious movements. Not only descriptive analysis, but also their thoughts and actions on existing religious organizations will be revealed. Fragmentation and contestation among Islamic mass organizations in order to gain public sympathy cannot be avoided. Moreover, the targets of their movement have led to practical political movements to gain positions and positions in power. According to him, power is the core target of their movement to make it easier to make community improvements or da'wah. The various currents of thought that occur in Muslims are a response to massive modernization. In the context of today's Indonesians, Islamic politics must be displayed with an Islamic spirit that is contemporary, intelligent, straightforward and takes sides with the efforts to uphold the values ​​of social justice. Every Islamic political thought will be tested by the contextualization in which Islamic political thought lives. Keywords: Radicalism, Islam, hardline, politics   Abstrak Tasikmalaya memiliki persoalan munculnya gerakan Islam garis keras, yang terkadang memunculkan wajah Islam “radikal”. Gerakan tersebut direspon oleh sebagian masyarakat, sehingga seolah mendapat dukungan rakyat. Mereka melakukan aktifitas sosial, politik dan pengerahan masa untuk menuntut hak-haknya dengan mengatasnamakan agama. Mereka melakukan tekanan terhadap pemerintah setempat dengan mengusung isu Perda syariat. Penelitian ini menelusuri beberapa organisasi masa Islam di Kota Santri, Tasikmalaya. Telaah riset terkait gerakan Islamis ini difokuskan pada polarisasi dan pragmentasi gerakannya, merepresentasikan tema diskursus terkait pemikiran dan aktifitas gerakan keagamaan. Bukan saja analisis deskripsi, namun akan diungkap juga pemikiran dan aksinya terhadap organisasi keagamaan yang ada. Fragmentasi dan kontestasi di antara ormas Islam guna meraih simpati masyarakat tidak bisa dihindari. Apalagi target-target gerakan mereka sudah mengarah pada gerakan politik praktis untuk memperoleh posisi dan kedudukan dalam kekuasaan. Menurutnya, kekuasaan merupakan inti target dari gerakan mereka untuk memudahkan melakukan perbaikan masyarakat atau dakwah. Berbagai arus pemikiran yang terjadi pada diri umat Islam merupakan respons terhadap modernisasi yang begitu masif. Dalam konteks ke-Indonesia-an hari ini, politik Islam mestilah bisa ditampilkan dengan semangat Islam yang menzaman, cerdas, lugas dan berpihak pada upaya tegaknya nilai-nilai keadilan sosial. Setiap pemikiran politik Islam akan diuji oleh kontekstualisasi di mana pemikiran politik Islam itu hidup. Kata kunci: Radikalisme, Islam, garis keras, politik